Processo de aprendizagem de uma nova prática na atividade de gestão em uma pequena empresa do comércio - Bello, Walderes de Lourdes (2009)
The present study aims at checking how the learning process of management new practices happened in a small commercial company in Curitiba, State of Paraná capital, in Brazil. The study is based on the supposition that small companies have a favorable environment to the learning process, due to its characteristics that facilitates such process. Small-size companies foster cooperation and involvement of all employees in their processes, what is an important factor to facilitate learning from a socio-cultural perspective. Based on the expansive learning theory suppositions and taking into consideration its ruling principles, we sought to assess the extent to which it is possible to observe the learning cycle in a small-size company. The study describes the environmental context, characteristics, activity system new practices and learning cycle, as well as the expansive learning process facilitating and limiting conditions in a Brazilian small-size company. To this end, our research is based on the case study method. The present study is experimental, exploratory and descriptive using crosscut with longitudinal verification. The research first carried out analysis of documents and secondary data contents, and then it analyzed narratives and direct observations. The research results showed that in the case study company: first, from the socio-cultural perspective there is organizational learning condition due to its learning-favorable environment; second, there is resistance to external influences, especially when coming from advanced systems; and third, the ruling staff centralize power thus permitting that all level-employees have just little participation in the decision-making process addressed to changes and new practices. Participation is a strong characteristic in small companies and motivates employees to be actively involved in the implementation and monitoring of new practices. We highlight that the multi-voicedness principle practice should be fostered so that everyone involved in the activity could express his opinion and suggestions thus contributing to create and enhance new activities.